Awareness of faraid among Muslim: a case study at Kuala Lipis, Pahang / Abdul Hannan Mohd Salehen - Mohd Salehen, Abdul Hannan (2022)
Faraid is one of the Islamic property dividing techniques. This faraid happens when a family member has passed away and is eligible to inherit the property. This faraid is one of the most crucial things to keep in mind in order to ensure that the property distribution programme operates successfully. The purpose of this study was to determine the degree of faraid awareness among Muslims in Kuala Lipis, to identify factors that impact faraid awareness, and to come up with ways to raise faraid knowledge among Muslims in Kuala Lipis. The quantitative technique was employed to finish this work. This strategy is utilised to meet all of the study's objectives as effectively as feasible. The majority of the respondents are aware of Faraid, hence the outcomes of this survey are encouraging. However, some people are still unaware of their surroundings.